Sparsentan versus Irbesartan in Focal Segmental Glomerulosclerosis - Rheault, Michelle N; Alpers, Charles E; Barratt, Jonathan; Bieler, Stewart; Canetta, Pietro; Chae, Dong-Wan; Coppock, Gaia; Diva, Ulysses; Gesualdo, Loreto; Heerspink, Hiddo J L; Inrig, Jula K; Kirsztajn, Gianna M; et al. (The New England journal of medicine, 2023)
BACKGROUND: An unmet need exists for focal segmental glomerulosclerosis (FSGS) treatment. In an 8-week, phase 2 trial, sparsentan, a dual endothelin-angiotensin receptor antagonist, reduced proteinuria in patients with FSGS. The efficacy and safety of longer-term treatment with sparsentan for FSGS are unknown. METHODS: In this phase 3 trial, we enrolled patients with FSGS (without known secondary causes) who were 8 to 75 years of age; patients were randomly assigned to receive sparsentan or irbesartan (active control) for 108 weeks. The surrogate efficacy end point assessed at the prespecified interim analysis at 36 weeks was the FSGS partial remission of proteinuria end point (defined as a urinary protein-to-creatinine ratio of ≤1.5 [with protein and creatinine both measured in grams] and a >40% reduction in the ratio from baseline). The primary efficacy end point was the estimated glomerular filtration rate (eGFR) slope at the time of the final analysis. The change in eGFR from baseline to 4 weeks after the end of treatment (week 112) was a secondary end point. Safety was also evaluated. RESULTS: A total of 371 patients underwent randomization: 184 were assigned to receive sparsentan and 187 to receive irbesartan. At 36 weeks, the percentage of patients with partial remission of proteinuria was 42.0% in the sparsentan group and 26.0% in the irbesartan group (P = 0.009), a response that was sustained through 108 weeks. At the time of the final analysis at week 108, there were no significant between-group differences in the eGFR slope; the between-group difference in total slope (day 1 to week 108) was 0.3 ml per minute per 1.73 m2 of body-surface area per year (95% confidence interval [CI], -1.7 to 2.4), and the between-group difference in the slope from week 6 to week 108 (i.e., chronic slope) was 0.9 ml per minute per 1.73 m2 per year (95% CI, -1.3 to 3.0). The mean change in eGFR from baseline to week 112 was -10.4 ml per minute per 1.73 m2 with sparsentan and -12.1 ml per minute per 1.73 m2 with irbesartan (difference, 1.8 ml per minute per 1.73 m2; 95% CI, -1.4 to 4.9). Sparsentan and irbesartan had similar safety profiles, and the frequency of adverse events was similar in the two groups. CONCLUSIONS: Among patients with FSGS, there were no significant between-group differences in eGFR slope at 108 weeks, despite a greater reduction in proteinuria with sparsentan than with irbesartan. (Funded by Travere Therapeutics; DUPLEX ClinicalTrials.gov number, NCT03493685.).
Keywords: senioři; hodnoty glomerulární filtrace; Remission Induction; mladiství; kreatinin; proteinurie; Middle Aged; Proteinuria; fokálně segmentální glomeruloskleróza; Adult; irbesartan; mladý dospělý; Irbesartan; dítě; Child; Young Adult; Humans; Glomerulosclerosis, Focal Segmental; biologické markery; lidé středního věku; indukce remise; Creatinine; dospělí; Biomarkers; Aged; Adolescent; lidé; Glomerular Filtration Rate